Phytochemical Analysis of Ashwagandha (Withania Somnifera) and its Role on Covid-19 –A Qualitative Review (AYUSHDHARA, 2021)
COVID-19 being a mild to severe respiratory and an infectious disease is caused by a new viral strain named coronavirus 2 (SARS-CoV-2). Though managed with antivirals such as lopinavir, ritonavir and nelfinavir, as well as the antimalarials chloroquine and hydroxychloroquine etc, none of them have provided the promising solution. Amidst these conventional approaches, bioactive natural compounds are being considered due to its good biocompatibility, bioavailability, less toxicity and rich phyto-constituents like phenols, steroids and flavonoid molecules etc. Ayurvedic system of medicine is the Ancient medicine that is being practiced since 5000yrs ago and Ashwagandha or Withania somnifera is being used as a rasayana in traditional medicine systems like Ayurveda, Unani, and Siddha. This has been known for its therapeutic benefits since long period including anticancer properties, neuro-protective, cardio-protective, hepato-protective, anti-inflammatory, anti-diabetic, antimicrobial, anti-arthritic, antistress/adaptogenic, chemo-/radiation sensitizing and immuno-modulatory properties etc. Currently Ashwagandha has been extensively studied using molecular docking approaches on Covid-19 due to its immuno-modulatory properties and Withania somnifera could be developed as a therapeutic agent against COVID-19 for both management and prevention.